1999
DOI: 10.1002/(sici)1097-0061(19990930)15:13<1357::aid-yea465>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Mouse CAF1, a mouse homologue of the yeastPOP2 gene, complements the yeastpop2 null mutation

Abstract: The yeast POP2 protein (Pop2p) is a component of a global transcription regulatory complex and is required for gene expression of many genes in Saccharomyces cerevisiae. We constructed POP2 deletion plasmids encoding various Pop2p regions under the native POP2 promoter and found that the minimum functional region was located in two‐thirds of the carboxyl terminal region. A mouse homologue of the POP2 gene (mCAF1), which corresponds to the Pop2p minimum region, partially rescued the growth defect of pop2 null m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…1 Because the mouse CAF1 (mCAF1) protein displays a greater homology to the canonical RNase motifs in the DEDDh family of proteins (17), we decided to characterize the putative deadenylase function of mCAF1. mCAF1 has also been shown previously to partially complement a ycaf1 deletion in yeast (21) and to interact very strongly with yeast CCR4 and NOT1 (11), 2 suggesting that it can act within a functional CCR4-NOT complex in vivo. To address the role of CAF1 in mRNA degradation, we have purified the mCAF1 to homogeneity and studied its in vitro and in vivo properties.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…1 Because the mouse CAF1 (mCAF1) protein displays a greater homology to the canonical RNase motifs in the DEDDh family of proteins (17), we decided to characterize the putative deadenylase function of mCAF1. mCAF1 has also been shown previously to partially complement a ycaf1 deletion in yeast (21) and to interact very strongly with yeast CCR4 and NOT1 (11), 2 suggesting that it can act within a functional CCR4-NOT complex in vivo. To address the role of CAF1 in mRNA degradation, we have purified the mCAF1 to homogeneity and studied its in vitro and in vivo properties.…”
mentioning
confidence: 71%
“…We also tested whether the deadenylase function of mCAF1 was required for complementing a caf1 deletion. A yCAF1/mCAF1 fusion (carrying the unique N-terminal of yCAF1 and the DEDDh domain of mCAF1) was used for this analysis, because it gives better complementation than does mCAF1 alone (21). We found that mCAF1 mutations (D39A/E41A and Y159A/D160A), which inactivated mCAF1 in vitro, like similar mutations in yCAF1 did not interfere with the ability of the yCAF1/mCAF1 hybrid protein to complement the caffeine sensitivity of a ycaf1 deletion (Fig.…”
Section: Table Imentioning
confidence: 93%
See 1 more Smart Citation